The Role of International Accounting Standards in Fostering Corporate Reporting Transparency - Poyda-Nosyk Nina; Pojda-Noszik Nina; Пойда-Носик Ніна; Robert Bacho; Bacsó Róbert; Бачо Роберт; Vyktorya Makarovych; Makarovics Viktória; Макарович Вікторія; Gabriella Loskorikh; Loszkorih Gabriella; Лоскоріх Габріелла; et al. (ТОВ Фінтехальянс, 2024)
Abstract. This research investigates the multifaceted impact of International Accounting Standards (IAS) on corporate reporting transparency. Amidst the interconnected global business landscape, the study aims to discern global adoption trends, financial reporting quality, stakeholder perceptions, implementation challenges, and the responsiveness of IAS to industry dynamics. Through meticulous analyses spanning the years 2010 to 2020, the research unfolds key insights. The adoption of IAS is a critical facet of global financial reporting, influencing business practices, investor decisions, and regulatory frameworks. Understanding its impact is paramount for policymakers, standard-setters, and businesses navigating an increasingly interconnected and diverse financial ecosystem. This research seeks to comprehensively examine the intricate relationship between IAS and corporate reporting transparency. By delving into adoption trends, financial metrics, stakeholder perspectives, implementation challenges, and update responsiveness, the study aims to provide a holistic view of the global accounting landscape. The analysis reveals a consistent upward trajectory in global IAS adoption, with North America and the Asia-Pacific region playing pivotal roles. Financial reporting quality experiences substantial improvements, particularly benefiting smaller enterprises. Stakeholder perceptions vary across regions and professional roles, emphasizing the need for tailored communication strategies. Implementation challenges, including legal framework complexities and cultural differences, underscore the intricate nature of global adoption. The frequency of IAS updates showcases the adaptability of standards to emerging trends, emphasizing sector-specific implications. This research concludes that IAS significantly influences corporate reporting transparency, offering a standardized framework for diverse business scales. Challenges in implementation necessitate targeted interventions, with recommendations focusing on stakeholder communication, tailored support for small enterprises, and addressing legal and cultural complexities. The adaptability of IAS to industry dynamics reaffirms its role as a responsive and evolving standard. As businesses, regulators, and standard-setters move forward, continuous collaboration and flexibility become imperative for navigating the complexities of a globally harmonized financial reporting landscape.
Роль міжнародних стандартів обліку в зміцненні прозорості звітності компаній
Редакційна колегія: https://fkd.net.ua/index.php/fkd/Editorial_Board
Зміст: https://fkd.net.ua/index.php/fkd/issue/view/71
Keywords: IAS; IFRS adoption; corporate reporting transparency; financial reporting quality; stakeholder perceptions